THE HISTORY OF THE FORMATION OF A SWIMMING SPORT IN UZBEKISTAN - Mo’ydinov Iqbol Abduxamidovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, we will consider the development of swimming sports in our country, the results achieved by our athletes in regional and international fields, as well as the stages of development among the population.